KONTRIBUSI OLAHRAGA FUTSAL TERHADAP MANFAAT BISNIS DAN KETERLIBATAN OLAHRAGA MASYARAKAT DI KOTA SALATIGA 2012 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Based on the observation, it shows that Futsal in Salatiga give the contribution in business benefit., in this case, the income of the owner of Futsal fields and sports shop in Salatiga. The increased of the 10 fields are : Arena increased 835,5%, Salatiga Futsal increased 190%, The Goal increased 112,4%, Putra Abadi increased 136,7%, Dipo Futsal increasedÂ  216,3%, Garasi increased 230%, Hantera increased 123,5%, Centro increased 190,8%, Kridanggo increased 192,9%, dan Planet increased 121,3%. The increased of the shops are : LOB increased 16%, Garuda Sport increased 17,5%, dan Gaya Baru increased 13,4%. The participants of Futsal in Salatiga are up to 29.100 people of 177.088 people in Salatiga every month. Â The conclusion of this research is Futsal contribute to the owner of Futsal fields, the owner of sports shop and the sports participant in Salatiga. The income of the owner of Futsal fields and sports shop increase because of Futsal. For people in Salatiga, Futsal contribute to increase the sport interest of people. Evidenced by 16,43% of all people in Salatiga. To interest the Futsal participants, the Futsal fields should be made as comfortable as possible, discount also advised for sports shop, and also more respect to Futsal by holding local competitions so it can get people attention